21st Century Classrooms and Work Performance of Public Elementary School Teachers - Delos Santos, Angie (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the extent of the effects of 21st-century classrooms on the work performance of public elementary school teachers in the Morong District, Division of Rizal, during the School Year 2025–2026. The study employed a descriptive survey research design complemented by documentary analysis. The respondents consisted of 286 public elementary school teachers from twelve schools in the district, selected through total population sampling. Data were gathered using a validated researcher-made questionnaire that assessed the perceived effects of 21st-century classrooms in terms of instructional delivery, classroom management, digital skills, and assessment of learning, as well as the challenges encountered by teachers. Teachers’ latest Individual Performance Commitment and Review (IPCR) ratings served as the basis for determining their level of work performance. Descriptive and inferential statistical tools were utilized to analyze the data. Findings revealed that the respondents were predominantly young adult, female, single teachers with Master’s degree units, mostly occupying Teacher II and Teacher III positions, having 10–14 years of teaching experience, and frequently attending district-level in-service trainings. Teachers perceived that 21st-century classrooms had a high effect on instructional delivery, classroom management, digital skills, and assessment of learning. However, no significant differences were found in these perceptions when grouped according to demographic characteristics. Teachers obtained a very satisfactory level of work performance based on their IPCR ratings. Furthermore, no significant relationship existed between the perceived effects of 21st-century classrooms and teachers’ work performance, although respondents reported occasionally encountering challenges in implementing 21st-century classroom practices. The study concluded that demographic variables did not significantly influence teachers’ perceptions of 21st-century classrooms, and these perceptions were not associated with their work performance. It is recommended that school administrators strengthen professional development initiatives focusing on innovative instructional strategies, student-centered classroom management, digital competence, formative assessment, and inclusive teaching practices. Teachers are likewise encouraged to continuously adopt learner-centered pedagogies and enhance their digital and instructional competencies. The proposed action plan is recommended for implementation, while future studies may explore additional variables affecting teacher performance in 21st-century learning environments..
Keywords: 21st-Century Classrooms, Work Performance, Public Elementary School Teachers, Instructional Delivery, Classroom Management, Digital Skills, Assessment Of Learning, IPCR, Descriptive Survey,.